Complementaridade e efetividade do comércio: o caso do nordeste e da Paraíba em relação ao Japão - Machado Neto, Pedro Augusto (2016)
Brazilian Northeast, in general, is at disadvantage in the new phase of Brazilian foreign trade, in which the country is strongly commodity-oriented, and that Paraíba, one of the deficient states of Northeast, can benefit directing its exports to Japan, a major underexplored importer market, in a scenario where the state is highly concentrated in a few products and partners. The general objective is, therefore, do a study on trade complementarity and effectiveness of the Northeast and Paraíba with Japan in the 2004- 2014 period. This is a quantitative study, and Trade Complementarity, Trade Effectiveness and Revealed Comparative Advantage indices calculations were made. The secondary database was taken from Aliceweb System, of Ministry of Development, Industry and Trade (MDIC), and TradeMap of World Trade Organization (WTO). It was found that the northeastern most successful states in the trade with Japan are those that export commodities, and those who do not have such an advantage, the case of Paraiba, have deficit. Paraíba’s underutilized sectors, for which there are comparative and complementary advantage, but there aren't commercially effectiveness, are "Prepared Foodstuffs, Beverages, And Tobacco","Textiles and textile articles", and "Articles of stone, ceramic products, glassware, etc”, and Northeast’s ones are "Raw Hides And Skins, Leather, Furskins And Articles", "Pulp Of Wood Or Of Other Fibrous Cellulosic Material", "Textiles and textile articles" and "Footwear, Headgear, etc.".